PENGARUH FUNGSI PELATIHAN, PEMODELAN PERAN DAN DUKUNGAN SOSIAL TERHADAP KEPUASAN KERJA PROTÉGÉS DALAM PEMENTORAN - RAINO WIRJONO, ENDANG (Jurnal Ilmiah Akuntansi dan Bisnis, 2007)
There has been considerable researches on mentoring. Recent studies about mentoring found that mentors provide coaching, social support and role modeling functions for protégés. Mentoring studies also found that these three functions affect protégés performance. This study aims at examining that the three functions of mentoring have significant impact on protégés job satisfaction The respondents of the study are accountants of the public accounting offices. There are 146 individuals participating in this study. Data is analyzed using multivariate regression analysis. Results of the study reveal that among the three mentoring functions, only role modeling function that has impact on protégés job satisfaction.
Keywords: mentoring activities, job satisfaction, protégés, mentor